Experiencia con el implante de levonorgestrel en el Hospital Nacional Cayetano Heredia. - Mauricio, P. (2015)
It has developed models of administration for steroidal contraceptives, alternative to oral,  requiring lower doses of steroids. The routes of administration are mainly subcutaneous, vaginal or intrauterine where devices from which slowly and predictably release contraceptive steroid is placed. One of these alternative models are levonorgestrel implants.